Image transmission with binary coding for free space optical communications in the presence of atmospheric turbulence - Huang, Xianwei; Bai, Yanfeng; Fu, Xiquan (Applied optics. Optical technology and biomedical optics, 2020)
Understanding the influence of atmospheric turbulence on optical information transmission is important for free space optical communication. In this paper, the image transmission through a 1 km horizontal turbulent channel has been numerically investigated, and a simulation model including the process of image pixels encoding and decoding is given. The peak signal-to-noise ratio of the received image is evaluated, and the influences of the channel factors and detector noise are discussed in detail. The critical value of noise level and turbulence strength is given. Our results provide a simulation model for image transmission in a turbulent channel along with insight into the impacts of turbulence parameters and detector noise, which are useful for applications in optical communication.